PENATALAKSANAAN DISFUNGSI MENELAN PADA PENDERITA STROKE AKUT DI UNIT STROKE - Sitti Airiza Ahmad* (NEURONA, 2011)
AIM TO IDENTIFY THE INCIDEMCE AND THE RECOVERY OF SWALLOWING FUNCTION IN ACUTE STROKE PATIENTS WHO WERE TREATED USING STANDARD METHOD IN UNIT STROKE DR CIPTO MANGUNKUSUMO HOSPITAL